IDENTITAS JEMAAH AHMADIYAH INDONESIA DALAM KONTEKS MULTIKULTURAL - Flavius Floris Andries; Mohtar Maso’ed; Zainal Abidin Bagir (Humaniora, 2014)
Jemaah Ahmadiyah Indonesia (JAI) is known as a group on behalf of themselves as part of Islam adherents, however, their acceptance as part of Islam become an issue led to the creation of conflict. Although by law, their existence in citizenship context is legal, but in public service is often made difficult, due to intervention of the interest groups and affiliate with the state. Disclaimer of JAI identity of Islam by Islamist group was not limited to the theological issues, dogmatic, but it extends to the social issues and public sphere policy. It can be found through postponement case of e-ID card service for the JAI community in Manis Lor village, Jalaksana District, Kuningan regency of West Java. By using a qualitative research methods, this research aims to identify and understand the basic reasons of the e-ID card service postponement for the JAI community and find out who the actor affecting these e-ID service postponement. Through interviews with several informant from government, that is executive, and legislative, and mass organizations were influential in the regency, and own JAI community, as well as document review, it was found that the e-ID services postponement for the JAI community in Kuningan West Java, was not apart from the role of local politics, Islamic mass organizations, thus it can be concluded that ID card services postponement for JAI in Kuningan are not limited to identity issue related to theological doctrine, but also the impact of the political bargaining at the local level related to the electoral votes winnings, and other parties to the influence of Islamic mass organizations that want to maintain status quo and power. Negotiation of interests between government and mass organization to make JAI as the power object led to discrimination against JAI as minorities in obtaining their rights as citizens.